Mortality of trauma patients in conflict-affected region: a retrospective observational study of ICU admissions and surgical management - Jacques Fadhili Bake; Phalek Kambere Mukama; Mumbere Kigayi Jean-Pierre; Kabuyaya Kakule Medard; Munyantwari Akomu Eugene (BMC Surgery)
Abstract Background Trauma represents a significant global health challenge, accounting for an estimated 4.4 million fatalities each year, predominantly affecting low- and middle-income countries (LMICs), especially those experiencing conflict. This research investigates the trends, treatment approaches, and outcomes of trauma patients within a mixed intensive care unit (ICU) at HEAL Africa Hospital located in North Kivu, Democratic Republic of Congo (DRC). Methods A retrospective cohort study was undertaken to evaluate data from 368 surgical patients who were admitted to the ICU of HEAL Africa Hospital from January 2021 to June 2023. The study gathered information regarding patient demographics, mechanisms of injury, diagnoses, management strategies, types of surgeries performed, utilization of mechanical ventilation, duration of hospital stay, and mortality rates. Data analysis was conducted using SPSS version 26, with categorical data expressed as frequencies. Statistical significance was evaluated using the chi-square test. Factors with a p-value of less than 0.25 in the bivariate analysis were then included in a multivariable logistic regression model. Results Among the 368 surgical patients, 167 (45.3%) were trauma cases, predominantly male (sex ratio 4.4:1) with a median age of 32 years. From these 167 cases, motor vehicle collision (MVC) (63.5%) and gunshot wounds (21.6%) were the leading causes of injury. Traumatic brain injury was the most common diagnosis (39.5%), and only 39.5% of patients underwent surgery. Mechanical ventilation was used in 30% of cases. The median length of stay was 2 days, and the overall mortality rate was 28.7%. Patients with extremity trauma were less likely to die while higher mortality rates were observed among mechanically ventilated patients (p < 0.001) and non-operated patients (p = 0.006). Conclusion This research underscores the considerable impact of trauma in areas affected by conflict and stresses the critical necessity for the enhancement of trauma care systems and the implementation of targeted interventions aimed at improving surgical outcomes in resource-limited environments. Trial registration: Not applicable